Trends in ophthalmology applicants going unmatched in the Canadian Resident Matching Service - Bondok, Mostafa; Bondok, Mohamed S; Law, Christine; Nathoo, Nawaaz; Damji, Karim F (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2024)
Background: Applicants to ophthalmology have high rates of going unmatched during the CaRMS process, but how this compares to other competitive or surgical specialties remains unclear. Our research aims to examine this phenomenon by identifying trends and comparing match data with other specialties, to identify disparities that may inform the need for future interventions to improve the match process for applicants.Methods: We used a cross-sectional analysis of data provided by CaRMS on the residency match from 2013 to 2022.Results: We obtained data from 608 ophthalmology, 5,153 surgery, and 3,092 top five (most competitive) specialty first choice applicants from 2013-2022. Ophthalmology applicants were more likely to go unmatched (18.9% [120/608]) than applicants to the top five (11.9% [371/3,092]) and surgical (13.5% [702/5,153]) specialties (p<0.001) and were twice as likely to rank no alternate disciplines (31.8%, p < 0.001) over the study period. In the first iteration, when alternate disciplines were ranked, the match rate to alternate disciplines was highest for ophthalmology applicants (0.41, p < 0.001). The majority (57.8%) of unmatched ophthalmology applicants do not participate in the second iteration.Conclusion: Compared to other competitive specialties, first choice ophthalmology applicants were more likely to go unmatched, rank no alternate disciplines, and choose not to participate in the second iteration. Ophthalmology applicant behaviours should be further studied to help explain these study findings.